The Role of Personality Factors in Predicting Resilience and Coping Styles of Patients with Type 2 Diabetes: A Cross-sectional Study - Reza Nemati; Hakimeh Vahedparast; Yaghob Rashedi; Kamran Mirzaei; Masoud Bahreini (Journal of Holistic Nursing and Midwifery)
Introduction: Diabetes is a serious, progressive, and costly disease that creates many limitations for its patient. Diabetes disrupts a person’s psychological and social adjustment and coping strategies, resulting in psychological complications for the patients. Objective: This study aims to determine the role of personality traits in predicting resilience and coping strategies of patients with type 2 diabetes living in Bushehr City, Iran. Materials and Methods: This cross-sectional study was performed on 120 patients with diabetes who were referred to healthcare centers in Bushehr. They were selected through the convenience sampling method. The study data were collected using the Connor-Davidson Resilience Scale, 60-item Neuroticism-Extraversion-Openness Personality Inventory, and Coping Strategies Questionnaire. In addition, descriptive statistics and linear regression tests were employed to interpret the data. Results: About 60.8% of the participants were female, and more than 90% were married and lived in urban areas. Based on the study’s results, there is a significant positive association between neuroticism and emotion-oriented (B=2.68, 95% CI; -0.666 to 4.701, P=0.01) and avoidance (B=2.60, 95% CI; -0.961 to 4.248, P=0.002) coping strategies. The results illustrated that neuroticism predicted resilience in patients with type 2 diabetes (B=-6.186, 95% CI; -11.632 to -0.741, P=0.026;), and the model predicted 9% of resilience (Adjusted R2=0.096). Conclusion: According to the results of the present study, most patients with type 2 diabetes had neuroticism, which could decrease their resilience. Therefore, due to the increasing trend of diabetic patients in Iran, and considering the etiological factors, it is necessary to pay attention to the psychological and personality components of these patients to know and adapt more to their physical and mental conditions.